Low identification of alcohol use disorders in general practice in England - Cheeta, Survjit; Drummond, Colin; Oyefeso, Adenekan; Phillips, Tom; Deluca, Paolo; Perryman, Katherine; Coulton, Simon (Addiction, 2008)
Aims: The prevalence of alcohol use disorders (AUDs) in the United Kingdom is estimated at 25%, and primary care has been identified as the first line of treatment for this population. However, there is a paucity of evidence regarding the current rates of identification of AUDs in primary care. The aim of the present study was to compare the observed rates of AUDs in general practice with expected rates, which are based on general population prevalence rates of AUDs. Design, participants and measurements: Epidemiological data on individuals aged 16-64 years with an AUD was obtained from the General Practice Research Database. General population prevalence rates of AUDs were obtained from the Psychiatric Morbidity Survey. χ 2 tests and identification ratios were used to analyse the data. Results: There was a significant relationship between type of AUD and identification (χ 2 = 1466.89, P < 0.001), and general practitioners were poorer at identifying harmful/hazardous drinkers when compared with dependent drinkers. No gender differences in the identification of hazardous/harmful drinking were found, but female dependent drinkers were significantly more likely to be identified than males (identification ratio 0.07; 95% confidence interval 0.06-0.07). The identification of AUDs was significantly lower for the 16-24-year age group compared with all other age groups. Conclusion: Despite attempts at targeting hazardous/harmful drinkers for brief interventions in primary care, the present findings suggest that this group are still under-identified. Furthermore, this under-identification is even more apparent in men and in young people who have high general population prevalence rates for AUDs. In conclusion, increasing identification rates could be incorporated into brief intervention strategies in primary care. © 2008 The Authors.
Keywords: Alcohol use disorders; Dependent drinking; General practice research database (GPRD); Hazardous/harmful drinking; Primary care; Psychiatric morbidity service (PMS)